2016
DOI: 10.11144/javeriana.uo35-74.urna
|View full text |Cite
|
Sign up to set email alerts
|

Uso de redes neuronales artificiales en predicción de morfología mandibular a través de variables craneomaxilares en una vista posteroanterior / Use of Artificial Neural Networks for Mandibular Morphology Prediction through Craniomaxillar Variables...

Abstract: <p><em><strong><span>Background:</span></strong></em><span class="apple-converted-space"><span> </span></span><span>Predicting mandibular morphology is important in facial reconstruction for forensic purposes as in orthodontics and maxillofacial surgery. This process has been performed through parametric and linear methods based on Caucasian populations. Also, these analyzes are performed on lateral cephalograms, but a prediction from a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…17 However, this situation is complicated when the mandibular defects affect almost the entire hemimandibular segment. The results of this work helps to improve aspects considered in previous researches about mandibular prediction, 8 and it can be established that the asymmetry is not only a property determined by the Mandibular shape asymmetry by EFA Niño-Sandoval et al size, but also the mandibular right curve is significantly dissimilar to the mandibular left curve. Taking this in to account to achieve a real mandibular prediction, asymmetry is a factor that must be considered in further studies.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…17 However, this situation is complicated when the mandibular defects affect almost the entire hemimandibular segment. The results of this work helps to improve aspects considered in previous researches about mandibular prediction, 8 and it can be established that the asymmetry is not only a property determined by the Mandibular shape asymmetry by EFA Niño-Sandoval et al size, but also the mandibular right curve is significantly dissimilar to the mandibular left curve. Taking this in to account to achieve a real mandibular prediction, asymmetry is a factor that must be considered in further studies.…”
Section: Discussionmentioning
confidence: 65%
“…In order to carry out a system accessible to the low-income Latin American population, that also has a proper mandibular morphology to the actual craniofacial conformation of the patient, it is proposed to employ two-dimensional elements such as analysis in panoramic radiographs to be extrapolated in a three-dimensional view. Approaches in prediction in other types of radiographs have been made in terms of size and position; 1,[4][5][6][7] however from a posteroanterior view according to a previous study, 8 a discrepancy could be observed between the left and right side prediction coefficients, with an important influence of the mandibular shape.…”
Section: Introductionmentioning
confidence: 99%